Rapid early coeval star formation and assembly of the most-massive galaxies in the Universe. Issue 4 (27th February 2020) - Rennehan, Douglas; Babul, Arif; Hayward, Christopher C; Bottrell, Connor; Hani, Maan H; Chapman, Scott C
Abstract: The current consensus on the formation and evolution of the brightest cluster galaxies is that their stellar mass forms early (z ≳ 4) in separate galaxies that then eventually assemble the main structure at late times (z ≲ 1). However, advances in observational techniques have led to the discovery of protoclusters out to z ∼ 7. If these protoclusters assemble rapidly in the early Universe, they should form the brightest cluster galaxies much earlier than suspected by the late-assembly picture. Using a combination of observationally constrained hydrodynamical and dark-matter-only simulations, we show that the stellar assembly time of a sub-set of brightest cluster galaxies occurs at high redshifts ( z > 3) rather than at low redshifts (z < 1), as is commonly thought. We find, using isolated non-cosmological hydrodynamical simulations, that highly overdense protoclusters assemble their stellar mass into brightest cluster galaxies within ∼1 Gyr of evolution – producing massive blue elliptical galaxies at high redshifts (z ≳ 1.5). We argue that there is a downsizing effect on the cluster scale wherein some of the brightest cluster galaxies in the cores of the most-massive clusters assemble earlier than those in lower mass clusters. In those clusters with z = 0 virial mass ≥ 5 × 10 14 M⊙, we find that 9.8 per cent have their cores assembly early, and a higher fraction of 16.4 per cent in those clusters above 10 15 M⊙ . The James Webb Space Telescope will be able to detect and confirm our prediction in the near future, and we discuss the implications to constraining the value of σ 8 .